Inversor multinível monofásico isolado de dois estágios aplicado no processamento da energia solar fotovoltaica em sistemas conectados à rede elétrica - Haura Junior, Remei (2017)
This work presents mathematical analyzes, simulations and construction of prototypes for a single-phase dual-stage photovoltaic inverter applied to the electronic processing of solar energy. Because it is a two-stage inverter, it consists of a DC-DC converter and a DC-AC converter. For the DC-DC converter, highlight the high-frequency galvanic isolation and the soft switching of the ZCS type obtained in the saturation and in the blocking of all the transistors of the structure. For the DC-AC converter, highlight the natural voltage clamping on all transistors corresponds to one half of the input bus voltage, the reduced voltage derivatives during switching and the three-level pulsed voltage obtained at its output. These are typical characteristics of the NPC multilevel inverter, proposed in this work for the first time in the composition of a dual-stage inverter. The use of the NPC inverter usually involves taking care of the symmetry of the voltages coming from the input DC bus capacitors, may involve modulation techniques or control for this purpose. In this proposal, the DC-DC converter, operating in open loop, imposes the symmetry of capacitor bus voltage of the NPC. All control of the two-stage inverter is concentrated in the DC-AC stage. This stage regulates the DC bus voltage and injects sinusoidal current into the commercial grid with unit power factor. Structure specifications: 2kW output power; PV array input voltage 400V; 127V rms AC output voltage; 20kHz switching frequency.